An analysis of the relationship between serum cortisol and serum sodium in routine clinical patients - Eleanor McLaughlan; Julian H. Barth (Practical Laboratory Medicine, 2017)
Objectives: Adrenal insufficiency is an uncommon cause of hyponatraemia that should not be overlooked due to the severe consequences of an Addisonian crisis. Using the laboratory database of a large teaching hospital, we have explored the relationship between serum sodium and serum cortisol, and have estimated the frequency of hypoadrenalism in severely hyponatraemic patients. Design and methods: Data were gathered over a 23 month period from the Laboratory Information Management System at the Leeds Teaching Hospitals NHS Trust for instances where serum sodium and cortisol had been measured on a single sample. Data were also gathered over the same time period for all patients with severe hyponatraemia (serum sodium ≤120 mmol/L) in order to determine the frequency of cortisol requesting and the incidence of adrenal insufficiency. Results: Analysis of the data (n=3268 patients) revealed a trend showing higher cortisol concentrations in patients who were severely hypo- or hypernatraemic. The median cortisol concentration for patients with sodium ≤110 mmol/L was 856 nmol/L, and there was a gradual decrease in cortisol over the sodium range ≤110–150 mmol/L (Rs =−0.323, p<0.0001). Patients with sodium ≥151 mmol/L had a median cortisol of 725 nmol/L. 42% of the 978 patients with serum sodium ≤120 mmol/L had serum cortisol measured within two weeks, of whom 1.7% were diagnosed with adrenal insufficiency. Conclusions: This dataset shows rising cortisol in response to hypo- or hypernatraemia, in keeping with the stress response to illness. The data show that adrenal insufficiency is a rare cause of hyponatraemia which may be overlooked. Keywords: Serum, Sodium, Cortisol, Adrenal insufficiency